'Ceremonies of renewal’: visits, relationships, and healing in the museum space - Laura, P (Berghahn Books, 2013)
Access to heritage objects in museum collections can play an important role in healing from colonial trauma for indigenous groups by facilitating strengthened connections to heritage, to ancestors, to kin and community members in the present, and to identity. This article analyzes how touch and other forms of sensory engagement with five historic Blackfoot shirts enabled Blackfoot people to address historical traumas and to engage in ‘ceremonies of renewal’, in which knowledge, relationships, and identity are strengthened and made the basis of well-being in the present. The project, which was a museum loan and exhibition with handling sessions before the shirts were placed on displays, implies the obligation of museums to provide culturally relevant forms of access to heritage objects for indigenous communities.